Management of perioperative anticoagulation in patients with mechanical heart valve replacement undergoing laparoscopic cholecystectomy: a case report of postoperative cerebral embolism - He, Wei; Tang, Panli (Frontiers in Surgery, 2024)
Patients with mechanical heart valve replacement require lifelong anticoagulation therapy, and additional surgeries can pose a risk of bleeding and thromboembolic events due to the need for perioperative anticoagulation management. Here, we present a case report of a patient who underwent laparoscopic cholecystectomy (LC) and endoscopic retrograde cholangiopancreatography (ERCP) after mechanical heart valve replacement and experienced postoperative cerebral embolism. The management of perioperative anticoagulation in these patients is discussed, including strategies for minimizing the risks of bleeding and thromboembolic events during and after surgery.